Pharmacovigilance study on the reporting frequency of atrial fibrillation with immune checkpoint inhibitors: insights from FDA Adverse Event Reporting System - Nunzia Balzano; Annamaria Mascolo; Donatella Ruggiero; Concetta Rafaniello; Giuseppe Paolisso; Francesco Rossi; Annalisa Capuano (Therapeutic Advances in Drug Safety)
Background: Immune checkpoint inhibitors (ICIs) have transformed cancer therapy but are linked with immune-related adverse events (irAEs), including cardiac events. Objective: This study aims to assess the reporting frequency of atrial fibrillation with ICIs using data from the Food and Drug Administration Adverse Event Reporting System (FAERS). Design: It is an observational, retrospective, pharmacovigilance study. Methods: Individual Case Safety Reports (ICSRs) were retrieved from FAERS up to September 24, 2024. Cases reporting one or more ICIs (atezolizumab, avelumab, cemiplimab, dostarlimab, durvalumab, ipilimumab, nivolumab, pembrolizumab, and tremelimumab) and atrial fibrillation were selected. Disproportionality analyses were performed by applying the reporting odds ratio (ROR) and the Informational Component (IC) with a 95% confidence interval (95% CI). Results: A total of 1228 ICSRs were retrieved, of which 218 (17.75%) were related to combinations of ICIs. Most ICSRs ( N  = 812; 66.1%) referred to male patients and the age group most represented was ⩾65 years ( N  = 772; 62.9%). Atrial fibrillation was serious in 99.3% ( N  = 1220) of cases and had a fatal outcome ( N  = 248; 20.3%). Atezolizumab, avelumab, durvalumab, nivolumab, and pembrolizumab were associated with a statistically significant higher reporting frequency of atrial fibrillation compared to all other drugs (ROR: 1.90, IC: 0.91; ROR: 1.94, IC: 0.92; ROR: 1.52, IC: 0.60; ROR: 1.30, IC: 0.38; ROR: 1.66, IC: 0.72, respectively). The anti-CTLA-4 ipilimumab showed a statistically significant lower reporting frequency of atrial fibrillation compared to all other drugs (ROR: 0.69, IC: −0.53) and to all other ICIs (ROR: 0.45, IC: −1.02). Moreover, anti-PD-L1 (ROR: 2.60, IC: 0.47) and anti-PD-1 (ROR: 2.12, IC: 0.16) were associated with a higher reporting of atrial fibrillation compared to anti-CTLA-4. Conclusion: ICI-induced atrial fibrillation was serious and had severe outcomes. The anti-CTLA-4 showed a lower likelihood of reporting atrial fibrillation, while higher reporting was found with anti-PD-1 and anti-PD-L1. Further studies are needed to confirm this safety aspect.